2020
DOI: 10.3390/nano10081489
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effect of Adding Nanoparticles to Polymer Flooding in Water-Wet Micromodels

Abstract: Recently, the combination of conventional chemical methods for enhanced oil recovery (EOR) and nanotechnology has received lots of attention. This experimental study explores the dynamic changes in the oil configuration due to the addition of nanoparticles (NPs) to biopolymer flooding. The tests were performed in water-wet micromodels using Xanthan Gum and Scleroglucan, and silica-based NPs in a secondary mode. The microfluidic setup was integrated with a microscope to capture the micro-scale fluid configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…A comparison of CeO 2 peaks by reference peaks shows a little shifting to larger angles can be attributed to positioning of the CeO 2 in the state of nanocomposite instead of nanoparticle form. Available peaks at the angle of 27.2° correspond to SiO 2 and the particle size is calculated as 27.5 nm [ 31 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of CeO 2 peaks by reference peaks shows a little shifting to larger angles can be attributed to positioning of the CeO 2 in the state of nanocomposite instead of nanoparticle form. Available peaks at the angle of 27.2° correspond to SiO 2 and the particle size is calculated as 27.5 nm [ 31 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oil recovery factor was up to 84%. Rueda et al [ 31 ] showed a beneficial and negative effect on the oil recovery factor when adding SiO 2 nanoparticles to the Xanthan gum and Scleroglucan biopolymers, respectively. The article [ 32 ] presents an analysis of the effect of the pore size distribution on the flow in the carbonate rock.…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of microfluidic studies on enhanced oil recovery using microfluidic experiments has shown that, to date, sufficient attention has been paid to studies on flooding using emulsions [ 18 ], surfactants [ 26 ], foams [ 14 ], and salt solutions [ 15 , 16 ], as well as microbial-enhanced oil recovery [ 30 ], polymer-enhanced oil recovery [ 21 , 31 ], and CO 2 -enhanced oil recovery [ 19 , 35 ]. However, very few works are devoted to the study of oil recovery using nanosuspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials, typically defined as suspensions with solid particles smaller than 100 nm, have the advantages of a high heat transfer capacity, large surface area, and low erosion and pressure drop compared to conventional suspensions, especially in microchannels. Many researchers have studied the application of nanomaterials alone or in combination with surfactants and polymers to enhance oil recovery [ 16 , 17 ], to delay the abandonment of old oil fields.…”
Section: Introductionmentioning
confidence: 99%